Investigation of Crucial Affected Proteins in Rat Liver in the Presence of Scrophularia - Vahid Mansouri; Babak Arjmand; Mahmood Khodadoost; Zahra Razzaghi; Mostafa Rezaei Tavirani*; Majid Rezaei Tavirani (Iranian Society of Pharmacognosy, 2023)
Background and objectives: Radix Scropholaria is dried root Scrophularia ningpoensis Hemsl. which is used uses as a drug against several diseases. In the present study, the crucial affected proteins of rat liver in the presence of radix Scrophularia have been investigated. Methods: The differentially expressed proteins (DEPs) were downloaded from literature. The significant DEPs plus 100 added first neighbors were determined and included in "protein query" of STRING database via Cytoscape software. The network was analyzed and the central nodes among the queried DEPs were identified. The 10 first neighbors of the central DEPs were determined. Results: RT1-CE12, Gfer, Serpina3c, Rab13, Rbm14, Ighg Psmb8, COX2, Olr796, Mga, Ugt1a6, Ugt2b, Ebpl, Ugt2b, Igf2r, and Amacr as significant DEPs were analyzed via protein-protein interaction (PPI) network analysis, Ugt1a1 and Ugt2b the two up-regulated proteins were highlighted as the crucial proteins in response to the radix Scrophularia. Conclusion: Two members of UDP glucuronosyltransferase family; Ugt1a1 and Ugt2b, were pointed as the critical liver enzyme which are dysregulated under effect of radix Scrophulariae. Due to crucial role of Ugt1a1 in the liver function, it is suggested that consumption of Scrophularia ningpoensis Hemsl. as a traditional medicine required more investigation.